An Interview with Adolf Muschg - Judith Ricker-Abderhalden (Studies in 20th & 21st Century Literature, 1984)
Adolf Muschg, a popular writer, teacher and aesthetician, is one of the comparatively few contemporary Swiss writers who has been able to establish himself firmly in Germany. In recent years, he has begun to attract the attention of American critics and Germanists as well. In the interview, Adolf Muschg deals with a wide spectrum of issues. He identifies the authors and works that mean most to him. He traces, for instance, his changing relationship to Goethe, whom he recently rediscovered. In Goethe's works, above all in his scientific studies, Muschg finds issues that are of central importance to the survival of our planet. He detects a kinship between Goethe and the "Greens" of the seventies and looks back critically on the turbulent sixties. He provides an analysis of the current tensions between the USA and Western Europe, while confirming his keen and very personal involvement with the USA. But at the core of the interview are his extensive comments on the creative processes and the perils inherent in writing fiction. There he deals with the complex relationship between literature and therapy, the therapeutic potential of literature for the writer and the reader. By describing the novelist's difficult journey on the narrow path between self-revelation and indiscretion, he also reflects upon the related issue of literary narcissism.
Keywords: Adolf Muschg; Swiss writer; Swiss; Germany; Goethe; scientific studies; Greens; 70s; 60s; environment; Western Europe; USA; literature; therapy; self-revelation; indiscretion; narcissism